EFFECT OF APPLING FLIPPED CLASSROOM ON ENGLISH ACHIEVEMENT OF PRIMARY 5 STUDENTS IN COVID-19 SITUATION - Phumphanit, Yupha; Rohmawati, Anisatur; Simpol, Wanida (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This research was collaboratively conducted with Indonesian students and aimed to 1) develop and evaluate the efficiency of Flipped Classroom management, 2) investigate the efficiency of Flipped Classroom management, and 3) examine learning achievement in English of Primary 5 students at Ban Nonkokkha school in Covid-19 situation. The target groups consisted of 32 students learning by using Flipped Classroom lesson plans in Covid-19 situation.  The Flipped Classroom lesson plan for teaching in Covid - 19 situation in semester 1 of Academic year 2021 were used to collect the data from June to October 2021. The research tools were Flipped Classroom lesson plans consisted of 12 plans for 12 hours, pretest and posttest. The data was analysed using descriptive statistics for data analysis including frequency, percentage, mean, standard deviation, average efficiency value, index of efficiency, and relative gain scores. The results of the research were as follows. 1) For the evaluation of the use of Flipped Classroom lesson plans for Primary 5 students, each of the lesson plans was averagely scored 3.67 – 4.33. Overall, the lesson plans were averagely scored at high level (x̄= 4.25, S.D.=0.60), the efficiency (E1/E2) was 83.03/78.54 which was higher than the preset criteria. 2) The index of efficiency of Flipped Classroom lesson plans was 0.6741, and the students' improvement increased 67.41 percent. 3) The students' learning achievement analysed from the relative gain scores of learning achievement results showed that the percentage of pretest scores was 34.17 whereas the percentage of posttest score was 78.54, and the percentage of growth score was 67.34 of which was interpreted as high level. When classifying based on the criteria, it was found that there were 7 students scored very high growth, 21 students’ high growth, and 4 students scored moderate growth.